Study of Important Blood Metabolites of Surti Goats under Different Estrus Synchronization Protocols - Yede, Amol B.; Khasatiya, Chandubhai T.; Singh, Virendra Kumar; Londhe, Arvind S.; Urkude, Atul (Indian Journal of Veterinary Sciences and Biotechnology, 2020)
Reproduction is the key to livestock production especially in goats that have high reproduction potential. Estrus synchronization is useful for rhythmic coordinated variation in reproductive hormones along with level of serum metabolites. Present study was conducted to evaluate variations of important blood biochemical metabolites in Surti goats under different estrus synchronization protocols. 18 Surti goats were divided equally (n=6) in 3 groups, viz., G1, G2 and G3 (control). G1 and G2 groups were injected i/m with GnRH analogue, Buserelin acetate 4.2 μg, on day 0 and 11 and PGF2α analogue, Dinoprost tromethamine 10 mg, on day 9. Progestogen sponge was also kept intravaginal in G1 group on day 0 and removed on day 11 before Buserelin injection. G3 group acted as control and received placebo of 2 ml normal saline simultaneous to treatment groups. Blood was collected on day 0, 5th, 11th, on the day of estrus and on day 30th post-estrus/mating for analysis of serum glucose, total protein and cholesterol. Levels of glucose, total protein and cholesterol varied non-significantly between groups, but within the group total cholesterol levels increased significantly (p <0.01) at 11th day of treatment and on the day of estrus with a drop on day 30th post-estrus, highlighting its role in estrus and pregnancy. On the day of estrus, coefficient of variation was minimum for cholesterol in both G1 and G2. Thus, it was concluded that synchronization protocols of GPG with intravaginal progestagen and GPG alone did not significantly alter serum glucose, total protein and cholesterol but effectively minimized variation of total cholesterol on the day of estrus.